Brucellae as resilient intracellular pathogens: epidemiology, host–pathogen interaction, recent genomics and proteomics approaches, and future perspectives - Dawood, Ali Sobhy; Elrashedy, Alyaa; Nayel, Mohamed; Salama, Akram; Guo, Aizhen; Zhao, Gang; Algharib, Samah Attia; Zaghawa, Ahmed; Zubair, Muhammed; Elsify, Ahmed; Mousa, Walid; Luo, Wanhe (Frontiers in Veterinary Science, 2023)
Brucellosis is considered one of the most hazardous zoonotic diseases all over the world. It causes formidable economic losses in developed as well as developing countries. Despite the significant attempts to get rid ofconquer Brucella pathogens in many parts of the world, the disease continues to spread widely. Recently, many attempts proved to be effective for the prevention and control of highly contagious bovine brucellosis, which could be followed by others to achieve a prosperous future without rampant Brucella pathogens. In this study, the updated view for worldwide Brucella distribution, possible predisposing factors for emerging Brucella pathogens, immune response and different types of Brucella vaccines, genomics and proteomics approaches incorporated recently in the field of brucellosis, and future perspectives for prevention and control of bovine brucellosis have been discussed comprehensively. So, the current study will be used as a guide for researchers in planning their future work, which will pave the way for a new world without these highly contagious pathogens that have been infecting and threatening the health of humans and terrestrial animals.